A reversible full adder using adiabatic superconductor logic. (31st January 2019) - Yamae, Taiki; Takeuchi, Naoki; Yoshikawa, Nobuyuki
Abstract: Reversible logic circuits can perform logic operations in a thermodynamically reversible manner, or without energy dissipation. The reversible quantum-flux-parametron (RQFP) is a reversible logic gate using adiabatic superconductor logic. In the present study, we design and demonstrate a reversible full adder (RFA) using RQFP gates in order to demonstrate that RQFP gates can be used as building blocks to design reversible logic circuits. An analysis of the time evolution of the phase differences across the Josephson junctions in the RFA showed that its logic state can change quasi-statically during a logic operation. Calculation of the energy dissipation of the RFA showed that it decreases in proportion to the operating frequency. These numerical calculation results ensure that the RFA is thermodynamically and logically reversible. In addition, we experimentally demonstrated correct operation of the RFA for all input data combinations. These results reveal that logic circuits designed using RQFP gates can perform reversible computing, i.e. RQFP gates can be used as building blocks of reversible logic circuits.